Pendampingan Penyusunan Harga Pokok Produksi Hasil Pengolahan Limbah Kain dalam Meningkatkan Perekonomian Kelompok Wanita Tani Salimah di Nagari Sungai Abang Kecamatan Lubuk Alung - Syafitri, Yulia; Asmeri, Rina; Yani, Meri; Silvera, Dica Lady; Anggraini, Meri Dwi; Hadya, Rizka; Delvianti, Delvianti; Bustari, Andre (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The aim of providing assistance to the community is to improve the skills of craftsmen in making products from fabric waste as well as preparing the cost of production of handicraft products. The method of community service is education with a lecture, discussion and practical work approach. The results obtained from this outreach activity are an increase in the digital knowledge and skills of KWT Salimah members regarding calculating the cost of production and the selling price of the production they produce. It is also hoped that this service will help them to care more about and protect the environment from pollution, especially from fabric waste and can also improve their skills by utilizing fabric scraps that are no longer usedabric waste and can also improve their skills by utilizing fabric scraps that are no longer used.